Positive Correlation Between Candida auris Skin-Colonization Burden and Environmental Contamination at a Ventilator-Capable Skilled Nursing Facility in Chicago. (12th May 2021) - Sexton, D Joseph; Bentz, Meghan L; Welsh, Rory M; Derado, Gordana; Furin, William; Rose, Laura J; Noble-Wang, Judith; Pacilli, Massimo; McPherson, Tristan D; Black, Stephanie; Kemble, Sarah K; Herzegh, Owen; et al.
Abstract: Background: Candida auris is an emerging multidrug-resistant yeast that contaminates healthcare environments causing healthcare-associated outbreaks. The mechanisms facilitating contamination are not established. Methods: C. auris was quantified in residents' bilateral axillary/inguinal composite skin swabs and environmental samples during a point-prevalence survey at a ventilator-capable skilled-nursing facility (vSNF A) with documented high colonization prevalence. Environmental samples were collected from all doorknobs, windowsills and handrails of each bed in 12 rooms. C. auris concentrations were measured using culture and C. auris -specific quantitative polymerase chain reaction (qPCR) The relationship between C. auris concentrations in residents' swabs and associated environmental samples were evaluated using Kendall's tau-b (τ b ) correlation coefficient. Results: C. auris was detected in 70/100 tested environmental samples and 31/57 tested resident skin swabs. The mean C. auris concentration in skin swabs was 1.22 × 10 5 cells/mL by culture and 1.08 × 10 6 cells/mL by qPCR. C. auris was detected on all handrails of beds occupied by colonized residents, as well as 10/24 doorknobs and 9/12 windowsills. A positive correlation was identified between the concentrations of C. auris in skin swabs and associated handrail samples based on culture (τ b = 0.54, P = .0004) and qPCR (τ b = 0.66, P = 3.83e −6 ). Two uncolonized residents resided in beds contaminated with C. auris . Conclusions: Colonized residents can have high C. auris burdens on their skin, which was positively related with contamination of their surrounding healthcare environment. These findings underscore the importance of hand hygiene, transmission-based precautions, and particularly environmental disinfection in preventing spread in healthcare facilities. Abstract : Candida auris causes healthcare-associated outbreaks that are difficult to control. Environmental contamination is common in these settings. At a ventilator-capable skilled-nursing facility, we found environmental contamination was positively related to the colonization burdens on associated residents' skin.